Nitrogen Preference for Growth Rate of Ulva raticulata cultivated in Eutrophied Coastal Waters: A Seaweed Laboratorium Testing Experiment - Sompa, Andi; Tuwo, Ambo; Lukman, Muhammad; Yasir, Inayah (International Journal of Environment, Agriculture and Biotechnology, 2019)
This study aims to evaluate seaweed Ulva raticulata preference for available nitrogen forms of eutrophic coastal waters for its growth rate. Simple experiment was developed for laboratorium testing of U. reaticulata preference for NH3, NO2, NO3 for 20 days. Levels of those nitrogen species and their composition were provided naturally from filtered eutrophic coastal waters of western coast of south Sulawesi Indonesia, without any exchange. The composition of NH3:NO2:NO3 in the eutrophic water of the experiment was 1.0 : 2.4 : 3.3. The results showed that the NO2 was the most preferred form of nitrogen for the growth. The average amount of uptake of NO2, NH3, and NO3 was respectively 4.58 ± 1.71 μg/l/day, 2.70 ± 0.17 μg/l/day, and 1.98 ± 1.19 μg/l/day. The average growth rate of U. reaticulata was 15.40 ± 3.12 % day-1.